Non-ideal Critical Realism Analysis on the Ethical Positions of Secular Doctors Towards Human Genome Editing - Albert Adiputra; Sindung Tjahyadi; Retna Siwi Padmawati (Jurnal Filsafat "WISDOM", 2023)
Human genome editing could be used to improve human intelligence, appearance, and physical strength. The ethical issues posed by the technology are causing public concern. Secularism views efforts to find moral truth do not depend on supernatural authority. The existence of a secular minority in Indonesia is considered an anomaly in public discourse and is left behind in the morally critical policy-making deliberations on genome editing regulations. The research explored Indonesian secular doctor’s view of human genome editing. This qualitative research used a non-ideal critical realism approach through in-depth interviews and literature review. Secular doctors say that human genomic editing has no different weight from other artificial selection. After conducting a risk-benefit analysis through moral calculus, secular doctors generally have positions and attitudes that support the research and implementation of human genomic editing technology.